A novel chemical genetic approach reveals paralog-specific role of ERK1/2 in mouse embryonic stem cell fate control - Hu, Liang; Xiao, Xiong; Huang, Wesley; Zhou, Tao; Chen, Weilu; Zhang, Chao; Ying, Qi-Long (Frontiers in Cell and Developmental Biology, 2024)
Mouse embryonic stem cells (ESCs) can be maintained and propagated in vitro through dual inhibition of two kinases, GSK3 and MEK. MEK has two highly homologous substrates, extracellular signal-regulated kinase 1 and 2 (ERK1/2). However, the exact role of ERK1/2 in ESC self-renewal and differentiation remains elusive. Here, we reveal that ERK1/2 are dispensable for ESC survival and self-renewal, and the inhibition of both ERK paralogs is sufficient to maintain ESC self-renewal when GSK3 is simultaneously inhibited. In contrast, knocking out either ERK1 or ERK2 cannot sustain ESC self-renewal. Furthermore, we introduce a novel chemical genetic approach to selectively inhibit ERK1 or ERK2, and find that inhibition of only one of the ERK paralogs is insufficient in mimicking the effect of MEK inhibitor in promoting ESC self-renewal. Regarding ESC differentiation, inhibition of ERK1/2 prevents mesendoderm differentiation. Additionally, selective inhibition of ERK1, but not ERK2, promotes mesendoderm differentiation. These results suggest that the two ERK isoforms have both overlapping and non-overlapping roles in regulating ESC self-renewal and differentiation.